Mojabanchromanol Isolated from Sargassum horneri Attenuates Particulate Matter Induced Inflammatory Responses via Suppressing TLR2/4/7-MAPK Signaling in MLE-12 Cells - Kalahe Hewage Iresha Nadeeka Madushani Herath (Marine Drugs, 2020)
Chromanols from marine algae are studied for drug development due to its prominent bioactive properties, and mojabanchromanol (MC), a chromanol isolated from a brown algae Sargassum horneri, is found to possess anti-oxidant potential. In this study, we hypothesized MC may attenuate particulate matter (PM)-induced and reactive oxygen species (ROS)-mediated inflammatory responses in airways and tried to identify its potential and underlying mechanism against PM (majority <2.5 µm in diameter)-induced inflammatory responses in a lung type II alveolar epithelial cell line, MLE-12. MC attenuated PM-induced malondialdehyde (MDA), a lipid peroxidation end product, and 8-hydroxydeoxyguanosine (8-OHdG), the most representative DNA oxidative damage product, further validating MC’s potential in attenuating PM-induced oxidative stress. MC also suppressed PM-triggered TLR2/4/7 activation in MLE-12 cells. Moreover, MC reduced ROS-mediated phosphorylation of mitogen-activated protein kinase (MAPK) extracellular signal-regulated kinase 1/2 (Erk1/2) and c-Jun NH (2)-terminal kinase (JNK) that were also activated in PM exposed cells. MC further inhibited the secretion of pro-inflammatory cytokines (IL-6, IL-1β and IL-33) in MLE-12 cells exposed to PM. These results provide a clear evidence for MC’s potential in attenuating PM-triggered inflammatory responses in MLE-12 cells via repressing TLR2/4/7 and MAPK signaling. Therefore, MC can be developed as a therapeutic agent against PM induced airway inflammatory responses.